Survey on fitness levels of wushu athletes at garuda fighting camp Palembang - Alza , M. Robby; Syafaruddin, Syafaruddin; Syamsuramel, Syamsuramel (Altius: Jurnal Ilmu Olahraga dan Kesehatan, 2024)
This research aims to determine the level of physical fitness of wushu athletes at the Garuda Fighting Camp Palembang club. The type of research used in this research is quantitative descriptive using survey methods through tests and measurements. The sample used in this research was 20 Garuda Fighting Camp wushu athletes aged between 16 and 19 years. This research uses a total sampling method, namely a sampling method where the number of samples and population used are the same. The data collection technique in this research uses a survey method and an aerobic endurance measurement test technique using the Indonesian Physical Fitness Test (TKJI) research results menu suggest that in the speed test component (60 m running) the athlete has a score of 7.50 which is in the good category. In the abdominal muscle strength component (Sit ups) male athletes had an average of 51.30, which is in the very good category. The athlete's hand muscle strength component (Pull ups) has a value of 12,750 which is in the medium category. The athlete's leg muscle explosive power component (vertical jump) has a value of 43.80, which is in the very poor category. The endurance component (1200 meter running) has a value of 6.9350 in the poor category. From the results of this research it can be concluded that the physical condition of the Garuda Fighting Camp Palembang club wushu athletes aged 16-19 is overall in the medium category, and still needs to be improved so that wushu athletes have better speed, strength, muscle endurance, explosive power and lung and heart endurance.